PENGARUH KINERJA LINGKUNGAN DAN PENGUNGKAPAN ESG TERHADAP NILAI PERUSAHAAN DAN KINERJA KEUANGAN PERUSAHAAN (Studi Empiris pada Perusahaan KOMPAS 100 yang Mengikuti PROPER Periode 2021-2023) - Muhammad Dafin Arkan Kusumo; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2025)
Corporate responsibility towards the environment has become an issue that has received great attention from various parties in recent years, along with the increasing environmental problems due to industrial development. Good corporate performance towards the environment is a crucial indicator for companies to gain legitimacy from the community which in turn has the potential to increase corporate value and financial performance. Transparent ESG disclosure is also a key factor tested by stakeholders which then has the potential to improve the company's reputation, attract investor interest, and have a positive impact on financial performance. This study aims to determine the effect of environmental performance and ESG disclosure on company value and company financial performance. The total sample used in this study was 72 samples, obtained from 24 companies listed in the KOMPAS 100 index in the 2021-2023 period and participating in PROPER in the same period. This study uses multiple linear regression analysis techniques and utilizes IBM SPSS 27 software. The independent variables in this study are enviromental performance as measured by the PROPER rating, and ESG disclosure as measured using the Bloomberg ESG score. The dependent variables in this study are company value as proxied using Tobin's Q, and financial performance as measured by ROA. The control variables in this study are company size.The results of the study indicate that environmental performance has a positive and significant effect on firm value and financial performance. Meanwhile, ESG disclosure does not have a significant effect on firm value, but has a negative and significant effect on financial performance. These findings provide new insights into the literature related to the effect of environmental performance and ESG disclosure on companies, as well as contributing to the management of environmental performance and corporate social responsibility. The limitations of this study include a limited sample of companies participating in PROPER and a limited time period, so that the long-term impact of ESG disclosure and environmental performance cannot be measured optimally.